MiR‐92a‐3p encapsulated in bone metastatic mammary tumor cell–derived extracellular vesicles modulates mature osteoclast longevity. Issue 12 (27th September 2022) - Uehara, Norihisa; Kyumoto‐Nakamura, Yukari; Mikami, Yoshikazu; Hayatsu, Manabu; Sonoda, Soichiro; Yamaza, Takayoshi; Kukita, Akiko; Kukita, Toshio
Abstract: Aberrant osteoclast formation and activation are the hallmarks of osteolytic metastasis. Extracellular vesicles (EVs), released from bone metastatic tumor cells, play a pivotal role in the progression of osteolytic lesions. However, the mechanisms through which tumor cell–derived EVs regulate osteoclast differentiation and function have not been fully elucidated. In this study, we found that 4T1 bone metastatic mouse mammary tumor cell–derived EVs (4T1‐EVs) are taken up by mouse bone marrow macrophages to facilitate osteoclastogenesis. Furthermore, treatment of mature osteoclasts with 4T1‐EVs promoted bone resorption, which was accompanied by enhanced survival of mature osteoclasts through the negative regulation of caspase‐3. By comparing the miRNA content in 4T1‐EVs with that in 67NR nonmetastatic mouse mammary tumor cell–derived EVs (67NR‐EVs), miR‐92a‐3p was identified as one of the most enriched miRNAs in 4T1‐EVs, and its transfer into mature osteoclasts significantly reduced apoptosis. Bioinformatic and Western blot analyses revealed that miR‐92a‐3p directly targeted phosphatase and tensin homolog (PTEN) in mature osteoclasts, resulting in increased levels of phospho‐Akt. Our findings provide novel insights into the EV‐mediated regulation of osteoclast survival through the transfer of miR‐92a‐3p, which enhances mature osteoclast survival via the Akt survival signaling pathway, thus promoting bone resorption. Abstract : This study investigated the effects of bone metastatic mammary tumor cell–derived extracellular vesicles (EVs) on the regulation of osteoclast differentiation and function. We found that bone metastatic mammary tumor cell–derived EVs and miR‐92a‐3p, the most enriched miRNA identified in these EVs, play pivotal roles in controlling mature osteoclast survival through inhibition of PTEN.